Se debe incorporar en el Código del Trabajo, el sistema de remuneración en especie en parte o en la totalidad de esta, como ya existe en otras legislaciones, modalidad que permitirá al trabajador participar de lo que produce la empresa - Draizel Noroña, Cristina Patricia (2015)
The wage compensation is one of the most important aspects of work that most directly affect the daily lives of workers, from its first years of existence, has revolved around the level of wages and workers have consistently fought to establish rules guarantee and protect the right to receive a fair wage. The obligation to pay the salary can basically fulfilled in two ways: in cash and or kind. Currently, wages in cash or cash is the most widely used of labor compensation, also in agricultural activities, however, the most characteristic aspect of policy on the remuneration of paid employment is surely the relative granting advantages unnatural, that is, those that consist of property other than money, all salary and extra-wage type, the causal connection with the employment contract is more or less intense, despite encontrarse in decline, subject significant restrictions, no doubt it is in rural areas where the payment of wages in kind has had and still has the longest tradition. Factors that may decide the perception by agricultural workers wage benefits in kind are varied and its customs; distance from the farms to the malls acquisition of consumer goods; poor liquidity of the employer; presence on farms of workers from other localities or regions specified board and lodging; the nature of the work to home to home, watchmen, guards running; Also, are almost endless situations that may be farm laborers; day laborers who come to the site of injury, remain there during the day and then return to your next home; home, guards continued provision of services with permanent staff throughout the year, to the employer, in addition to the cash salary, housing and / or a small plot for personal cultivation provides; the rustic servant or domestic servant who work daily, weekly or monthly amount is payable, and provided with food, sleeping in the home of the employer or any of its agencies; d) the pastor, only overnight in your own home once a week or fortnight, receives some essential supplies and spends the night in the place where enclosing livestock, often in the wilderness or in the mountains; e) seasonal come from different places (reapers, harvesters, harvesters ...) whom the employer provides the raw materials needed to make their meals together and sleep in the house used as shelter or bedrooms authorized by the company, etc. Benefits in kind that are used to repay the paid labor in agriculture can take different forms; maintenance (room and board) for workers who live in your own home of the employer; assignment of independent living for a worker and family; supplying a part of the products of the crop (wheat, milk, vegetables); authorize the employee to own cattle breeding cattle mixed with the employer; assignment of usufruct of land (orchard, pasture); Elsewhere: firewood or fuel wood, hay, straw, water, electricity. In any case, the Ordinance currently shows a clear preference for the salary which is payable in cash, establishing quantitative and qualitative perceptions sort of way that is not burdensome for workers limitations. In colonial times, especially in Ecuador where the Spaniards invaded applied some forms of payment in order that the income of the colonizer not decrease and that is why cunningly initially established in mining, agriculture, livestock from the system to , in which the mine owner, land and livestock, gave workers so that makes it produce and what occurred, month, or year is divided equally, then came the other form of payment which is my subject is either the owner of the mine, land, gave the worker or as it was called leaning of the estate to make it produce in exchange for this effort leaning received as part payment of wages staples for the consumption of his family, because in those days the patterns were the owners of all staples, I think now you can also apply this kind of payment agreement between employer and employee which they latter would become the first customers of the companies of their products at affordable prices